Novel metaphor processing in dyslexia: a visual world eye-tracking study - Cersosimo, Rita; Engelhardt, Paul E.; Fernandez, Leigh; Domaneschi, Filippo (Discourse processes, 2025)
Metaphor comprehension has been investigated in neurodevelopmental disorders, but studies devoted to adults with dyslexia are few and present inconsistent results. The present study sought to investigate how adults with dyslexia process novel metaphors. Individual differences in vocabulary, working memory, and Theory of Mind were also assessed. An online metaphor comprehension task based on the Visual World Paradigm was carried out with eye-tracking. Metaphors and corresponding literal sentences were aurally presented in isolation, and participants were asked to select a picture that best corresponded to the sentence they heard. Our results indicated that participants with dyslexia chose metaphor interpretations at a similar rate as did the control group. However, online processing data indicated generally slower response times, with a particular delay in processing metaphorical utterances. Eye movement analyses provided further insights into the underlying nature of the processing slowdowns, highlighting specific challenges encountered by individuals with dyslexia when interpreting figurative language.